The mediating role of marketing management in the relationship between online presence and product innovation among SMEs - Perez-Orozco, Allan (2024)
Purpose: This study explores the mediating role of marketing management in the relationship between online presence and product innovation among Small and Medium Enterprises (SMEs). Design/methodology/approach: The sample comprises 205 Costa Rican SMEs collected by the Global Competitiveness Project during the first half of 2019. The data were analyzed using a two-stage modeling strategy for ordinary regression models to analyze mediation effects. Findings: Marketing management as a strategic resource or capability accounts for the relationship between online presence and product innovation performance in SMEs, meaning that online presence resources require complementary organizational capabilities in marketing management to enhance product innovation. Originality/value: This study, grounded in the resource-based view theory, contributes to the innovation field by identifying marketing management capabilities as an intermediate strategic interaction between online presence and product innovation performance in SMEs. Thus, managers should recognize the advantages of integrating marketing management principles and tactics into online presence tools to realize the value of their products by tailoring them to their client’s needs.